Real Estate Investing: Market Analysis, Valuation Techniques, and Risk Management - Manganelli, Benedetto (Springer, 2015)
This book describes in full the major approaches used to evaluate investment in real estate and shows how theory informs decision-aid methods and tools to support such evaluation. The inclusion of numerous examples makes it also a practical guide to assessing the suitability of an investment property.